Kids, wealth, and consequences : ensuring a responsible financial future for the next generation - Morris, Richard A.; Pearl, Jayne A. , 1954- (Bloomberg Press, 2010)
"High-net-worth individuals learn how to pass on financial, intellectual, and emotional capital to their children, leaving them responsible, well-adjusted stewards of that wealth. This book enlightens high-net-worth parents about the unique issues they must explore. It addresses "hard" financial issues such as investing and estate planning and "soft" emotional issues such as values, family, and communication"--Provided by publisher